OLS regression - Leong, Ivan Shih Lun. (2011)
Regression is a common statistical technique used to allow one to ascertain if a relationship exists between a dependent variable that is of interest with one or more independent variables, and goes a step further to predict this dependent variable of interest with past data. This Final Year Project (FYP) approaches regression through understanding the method to come out with a validated regression model, and finally this is utilized on a real-life scenario with a person’s income as the dependent variable of interest. Thereafter, the results are presented with suggestions on further improvement.